Codigestão de água residuária de fecularia de mandioca em reator contínuo de tubos múltiplos: efeito do percentual de glicerol sobre a produção de BioH2 - Rossi, Luana Cristina Calliari Leite (2023)
The anaerobic co-digestion of substrates promotes the stabilization of residues that often present difficulties for biodigestion, increasing the efficiency of biogas production. Studies with real effluent from cassava starch supplemented with glycerol from biodiesel were conducted in some types of reactors and demonstrated that the co-digestion of these residues improved the performance of hydrogen production. In this context, the objective of the present study was to evaluate the production of hydrogen from MRA supplemented with glycerol from biodiesel in a continuous multi-tube reactor (RCTM), verifying the effect of increased glycerol dosage on hydrogen production and reactor stability. The profiles of metabolites generated in the process as a function of glycerol dosage were also evaluated. The RCTM is composed of 12 parallel tubes through which the liquid flows, consisting of 3 chambers: inlet chamber, intermediate region, and outlet chamber, with a useful volume of 1.13 mL and an area of tube walls of 2.511 cm². The reactor was inoculated with thermally treated anaerobic sludge (95 °C, 15 minutes) from a sanitary sewage treatment system. The RCTM was fed with wastewater from the cassava starch industry supplemented with glycerol at dosages of 1.5 and 3.0% (v/v) and operated under two conditions of volumetric organic load (VOC 39.1 and 74.6 gCOD L-1 .d-1 ), with fixed TDH of 4 h and temperature of 30 degrees. The experimental conditions evaluated were: C1: 1.5% and VOC of 74.6 gCOD L-1 .d-1 ; C2: 3.0% and VOC of 74.6 gCOD L-1 .d-1 ; C3: 1.5% and VOC of 39.1 gCOD L-1 .d-1 and C4: 3.0% and VOC of 39.1 gCOD L-1 .d-1 ). The main metabolites quantified under all operating conditions were lactic and acetic acids. The average performance of each condition conducted in the RCTM was evaluated by means of the indicators biogas flow (Qbiogas, in mL d-1 ) C1 = 1264.54; C2 = 23.48; C3 = 506.08 and C4 = 88.99, volumetric production of hydrogen (PVH2 in mL H2 L -1 d -1 ) C1 = 161.33; C2 = 0.00; C3 = 109.46 and C4 = 0.00, molar flow rate of hydrogen (VMH, in mmol H2 d -1 ) C1 = 15.85; C2 = 0.00; C3 = 1.91 and C4 = 0.00 and hydrogen yield (YH2, in mmol H2. mol-1 sucrose) C1 = 16.33; C2 = 0.00; C3 = 15.27 and C4 = 0.00, proportion of hydrogen (H2 (biogas) (%) C1 = 14.72; C2 = 0.04; C3 = 8.55 and C4 = 0.28. From the present study, it is concluded that despite the great instability, the RCTM produced biohydrogen, with the presence of methane in the biogas. The highest PVH2 (808.49 mL H2 L -1 d -1 ) occurred in C3 (1.5% glycerol and VOC of 39.1 gCOD L-1 .d-1 ).